The image of the author of a scientific text as a subject of imagology: Образ автора научного текста как предмет имагологии - Baklanova, Irina (Przegląd Wschodnioeuropejski, 2020)
The article discusses linguistic methods for determining the images of authors of scientific texts. The theoretical basis of the study is a typology of points of view reflected in the text. The research method consists in detecting implicatures in the content of the text and determining their relationship to the author’s intentions. The image of the author is derived on the basis of the assessments, language means and the stated facts contained in the text. On the basis of implicatures, the content of which does not contradict the author’s intentions, his intentional image is derived. In the presence of implicatures, which most likely do not correspond to the author’s intentions, the perceptual image of the author is determined.